2013
DOI: 10.1186/1471-2334-13-512
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity against Toxoplasma gondiiinduced by DNA immunization with the gene encoding a novel vaccine candidate: calcium-dependent protein kinase 3

Abstract: BackgroundToxoplasma gondii can infect almost all warm-blood animals including human beings. The plant-like calcium-dependent protein kinases (CDPKs) harbored by T. gondii are involved in gliding motility, cell invasion, egress and some other developmental processes, and so have been implicated as important virulence factors.MethodsIn the present study, we constructed a DNA vaccine expressing T. gondii CDPK3 (TgCDPK3) and evaluated its protective efficacy against T. gondii infection in Kunming mice. The gene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
6
26
0
Order By: Relevance
“…In the chronic toxoplasmosis model, a statistically significant reduction in the tissue cyst count was found in both vaccinated subgroups. This is similar to the results of Zhang et al (2013) using gene encoding calcium dependent protein kinase 3 in mice immunization, Makino et al (2011) using Toxoplasma gondii heat shock protein 70 gene, Rabie et al (2003) using heat shock protein 70 gene, heat shock protein 30 and SAG genes and Angus et al (2000) using surface antigen incorporated within a plasmid vector in immunization of mice. On the other hand, a lower percentage of cyst reduction was reported by Martin et al (2004) using granular and rhoptery proteins in combination with alum as a vaccine adjuvant.…”
Section: Discussionsupporting
confidence: 72%
“…In the chronic toxoplasmosis model, a statistically significant reduction in the tissue cyst count was found in both vaccinated subgroups. This is similar to the results of Zhang et al (2013) using gene encoding calcium dependent protein kinase 3 in mice immunization, Makino et al (2011) using Toxoplasma gondii heat shock protein 70 gene, Rabie et al (2003) using heat shock protein 70 gene, heat shock protein 30 and SAG genes and Angus et al (2000) using surface antigen incorporated within a plasmid vector in immunization of mice. On the other hand, a lower percentage of cyst reduction was reported by Martin et al (2004) using granular and rhoptery proteins in combination with alum as a vaccine adjuvant.…”
Section: Discussionsupporting
confidence: 72%
“…Our results showed that the level of anti-T. gondii IgG antibodies in mice immunized with pVAX-CDPK5 was statistically significantly elevated compared with levels in the three control groups. However, antibody titers in sera from the immunized mice, following three immunizations, were only twice as high as those in control mice, an antibody level which is much lower than those elicited by eukaryotic initiation factor 4A (eIF4A), rhoptry protein 18 (ROP18), microneme protein 6 (MIC6), and other T. gondii vaccine candidates (18,22,24,25,32,33). Because IgGdependent phagocytosis, cytotoxicity, or complement-mediated lysis effects are crucial mechanisms for resistance to tachyzoites (31), the relatively low antibody levels resulting from DNA immunization with pVAX-CDPK5 failed to prevent acute infection.…”
Section: Discussionmentioning
confidence: 99%
“…Our unpublished data and previous studies showed that both TgCDPK1 and TgCDPK3 (22) are promising vaccine candidates that can elicit protective immunity against acute and chronic T. gondii infection, but the immunogenicity of other CDPK members is not yet known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, TgCDPK1, TgCDPK3, and TgCDPK7 were shown to participate in parasite motility, such as host-cell invasion and egress, and parasite division and growth (Lourido et al, 2011(Lourido et al, , 2012McCoy et al, 2012;Morlon-Guyot et al, 2014). The important functions and the low variation of CDPKs in different T. gondii strains imply that they may be considered promising vaccine candidates, as the protective immunity induced by T. gondii CDPK3 revealed in our previous study showed the suitability of this protein family for development of new vaccines against T. gondii parasite infection (Zhang et al, 2013).…”
Section: Resultsmentioning
confidence: 97%